Preparation of Benzaldehyde by Liquid-Phase Catalytic Oxidation of Methyl Benzene - Peng, Ge; Liu, Wangcai; Li, Qiuping; Zhang, Haojian; Huang, Hui (Asian Journal of Chemistry, 2014)
One of the most important process in the field of petrochemical industry is that hydrocarbons are oxidized to aldehydes and acids using organic acid as solvent in the presence of catalysts consisting of cobalt acetate, manganese acetate and bromine compounds. The liquid phase catalytic oxidation of methyl benzene is discussed in this paper. The experiments are carried out in both pure methyl benzene and in solvents. During the process of liquid-phase catalytic oxidation of pure methyl benzene, the catalytic efficacies of different catalysts were not very significant. The addition of bromine significantly improve the catalytic efficiency. The rates of oxidation of methyl benzene in solvents were significantly higher than that in pure methyl benzene and the yield of benzaidehyde is improved.